MORALITY VALUES IN JUMBO MOVIE SOUNDTRACK SONGS AND THEIR RELEVANCE TO INDONESIAN LANGUAGE LEARNING AT MADRASAH ALIYAH - Endang (2025)
Songs as modern literary works not only function as entertainment, but also as a means of character education, one of which can be found in the soundtrack of the movie Jumbo. This research aims to reveal the morality values in Jumbo movie soundtrack and its relevance to Indonesian language learning in Madrasah Aliyah. This research uses descriptive qualitative approach with literature study method which is analyzed through Miles & Huberman interactive model. The data is in the form of lyrics of three main songs part of the soundtrack of this movie, namely Selalu Ada di Nadimu sung by Bunga Citra Lestari, Prince Poetiray & Quinn Salman, Dengar Hatimu by Prince Poetiray & Quinn Salman, and Kumpul Bocah by MALIQ & D'Essentials. The research found seven prominent morality values, namely gratitude, compassion, caring, resilience and courage, optimism, self-awareness, and cultural preservation. These values are in line with Lickona's character education framework that emphasizes the integration of moral knowing, moral feeling, and moral action. The conclusion of this study confirms that the soundtrack song can be an effective medium for Phase F Learning Outcomes (CP) for grades XI-XII, namely evaluating song texts as literary texts, appreciating the aesthetic quality of lyrics, and writing reflections or literary creations inspired by songs. This also strengthens the implementation of the Merdeka Curriculum, supports the achievement of the Pancasila Student Profile, and reflects the vision of Islamic education Rahmatan lil 'Alamin. Thus, this research confirms the position of songs as a bridge between literary appreciation, character strengthening, and contextual learning in the digital era.